CTLA4-Ig interferes and downregulates the proinflammatory activities of rheumatoid synovial macrophages in monoculture - L. Felli; L. Molfetta; P. Clerico; P.F. Triolo; B. Villaggio; B. Seriolo; A. Sulli; P. Montagna; S. Soldano; R. Brizzolara; M. Cutolo (Reumatismo, 2011)
Objective: CTLA4-Ig, a biologic agent employed in rheumatoid arthritis (RA) treatment, downregulates the immune response and exerts anti-inflammatory effects acting on different cells including dendritic/T cells interaction and directly on osteoclasts. We investigated the anti-inflammatory effects of CTLA4-Ig in primary monocultures of RA synovial macrophages (SM). Methods SM were obtained, from 8 RA patients (7 F, 1 M; DAS28>5.2) who underwent therapeutic arthroscopic synoviectomy and were cultured in the absence and in the presence of CTLA4-Ig at the concentration of [500 μg/ml], the most reliable dose related to the previous pharmacological clinical and experimental experiences. Inflammatory cytokine (IL-6, TNFalpha, IL-1beta) expression was evaluated by immunocytochemistry (ICC with relative image analysis), western blot (WB), and quantitative real-time polymerase chain reaction (qRT-PCR). Results: ICC analysis revealed that CTLA4-Ig treatment significantly downregulated cytokine expression (p<0.001 for IL-6, TNFalpha and IL-1beta) when compared to untreated RA SM. WB and qRT-PCR confirmed partially the data. Conclusions: CTLA4-Ig was found to exert a direct and significant anti-inflammatory effect on primary monocultures of RA SM, suggesting a therapeutic power in different phases of the disease activity.